A generative neural network based on a hetero-encoder model for de novo design of potential anticancer drugs: application to Bcr-Abl tyrosine kinase - A. D. Karpenko; T. D. Vaitko; A. V. Tuzikov; A. M. Andrianov (Informatika)
Objectives. The problem of developing a generative hetero-encoder model for computer-aided design of potential inhibitors of Bcr-Abl tyrosine kinase, an enzyme whose activity is the pathophysiological cause of chronic myeloid leukemia, is being solved.Methods. A generative hetero-encoder model was designed based on the recurrent and fully connected neural networks of direct propagation. Training and testing of this model were carried out on a set of chemical compounds containing 2-arylaminopyrimidine, which is present as the main pharmacophore in the structures of many small-molecule inhibitors of protein kinases.Results. The developed neural network was tested in the process of generating a wide range of new molecules and subsequent analysis of their chemical affinity for Bcr-Abl tyrosine kinase using molecular docking methods.Conclusion. It is shown that the developed neural network is a promising mathematical model for de novo design of small molecules which are potentially active against Bcr-Abl tyrosine kinase and can be used to develop effective broad-spectrum anticancer drugs.